2011
DOI: 10.1097/rlu.0b013e31820aa165
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body FDG PET/CT in Diagnosis of Internal Mammary Nodal Metastasis of Ovarian Carcinosarcoma

Abstract: Internal mammary lymph node is rare metastatic site in ovarian neoplasm. In this study, we report an ovarian carcinosarcoma with peritoneal carcinomatosis initially. Annually, whole-body FDG PET/CT is indicated during 4 years. Tiny peritoneal nodules are found on the first-time FDG PET/CT imaging. A high grade of FDG-avid internal mammary nodal activity is shown on the secondary time of FDG PET/CT imaging. Pathologic result of excision biopsy demonstrates carcinoma metastasis. On the recent imaging, significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…CT examination of patients with OMMMT found that most tumors showed unilateral large cystic solid masses with moderate or high enhancement, and the apparent diffusion coefficient of solid components was relatively high [ 29 ]. The PET/CT scan was useful for the detection of metastatic lesions, and a case of OMMMT patient who benefited from early detection of breast lymph node metastasis with PET was reported [ 31 ]. Researches suggested that CA125 was closely correlated with the prognosis of OMMMT patients [ 18 ], and study proposed that preoperative CA-125 levels exceeding 75 U/ml predicted a poor prognosis [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…CT examination of patients with OMMMT found that most tumors showed unilateral large cystic solid masses with moderate or high enhancement, and the apparent diffusion coefficient of solid components was relatively high [ 29 ]. The PET/CT scan was useful for the detection of metastatic lesions, and a case of OMMMT patient who benefited from early detection of breast lymph node metastasis with PET was reported [ 31 ]. Researches suggested that CA125 was closely correlated with the prognosis of OMMMT patients [ 18 ], and study proposed that preoperative CA-125 levels exceeding 75 U/ml predicted a poor prognosis [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The earliest report of ovarian cancer metastasis to an IMN involved a 30‐year‐old woman with a stage I mucinous tumor (see Table ) . Since that report in 2000, eight articles have been published involving 23 additional women . Demographic, medical, and treatment characteristics of these women are summarized in Table to aid in comparing those cases to the one reported herein.…”
Section: Case Reports and Case Series Of Ovarian Cancer Metastases Tomentioning
confidence: 99%